Tabloidyzacja czy tabloidyzacje telewizyjnych programów informacyjnych? (Fakty TVN i Wiadomości TVP) - Hordecki, Bartosz; Piontek, Dorota (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
Tabloidization is one of the main processes affecting modern mass media which can be observed in the media systems around the world. In Poland, the phenomenon of tabloidization has clearly intensified since the emergence of a pluralist media market, and in particular since the first commercial TV station and first typical tabloid have come into existence. The objective of the paper is to present the tabloidization processes in the Polish system of TV broadcasting. Having narrowed the subject matter to the realm of news programs the authors present the research conducted in order to address two fundamental questions: 1. Does the tabloidization of TV programs in Poland occur irrespective of the broadcaster’s status, and 2. Is the tabloidization of TV programs different depending on the broadcaster’s status?